Review of knowledge management in higher education - Altaf Haqani, Alyami Effra; Ahlan, Abdul Rahman (International Journal of Science and Research, 2015)
Higher educational institutions (HEIs) generate and implement Knowledge amid their procedures and activities. Utilising this Knowledge Management and innovations in higher education is as fundamental as it is in the corporate sector. If it is implemented successfully, it can prompt better decision making capacities, lessened "Product" development cycle duration (for instance, educational modules improvement and examination), enhanced scholastic and administrative Services, and diminished expenses. The objective for the paper is to emphasise and show a review of the requirement for knowledge management in higher educational institutions and to throw some light on the impact on institutions, if the knowledge that is delivered is not captured properly could lead to the phenomenon of “knowledge drain”, particularly the tacit knowledge that resides in the minds of the people. This results in loss of useful knowledge from the Organisation.